2022
DOI: 10.1093/cid/ciac354
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Rapid Molecular Test for Klebsiella pneumoniae Carbapenemase and Ceftazidime-Avibactam Use on Outcomes After Bacteremia Caused by Carbapenem-Resistant Enterobacterales

Abstract: Background Patients with bacteremia due to carbapenem-resistant Enterobacterales (CRE) experience delays until appropriate therapy and high mortality rates. Rapid molecular diagnostics for carbapenemases and new β-lactam/β-lactamase inhibitors may improve outcomes. Methods We conducted an observational study of patients with CRE bacteremia from 2016-2018 at eight New York and New Jersey medical centers and assessed center-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 37 publications
0
42
0
1
Order By: Relevance
“…Chronic dialysis may also be an area for further investigation with antibiotic dosing to improve outcomes among CRE infections due to its especially high association with clinical failure. Rapid diagnostics and aggressive antibiotic use early in disease may be warranted for these high-risk characteristics among CRE infections, with recent research in CRE bacteremia showing positive outcomes ( 25 ). Research should continue on carbapenem-resistant Enterobacterales infections in large, randomized cohorts and case-control studies to further identify best practices to promote treatment success.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic dialysis may also be an area for further investigation with antibiotic dosing to improve outcomes among CRE infections due to its especially high association with clinical failure. Rapid diagnostics and aggressive antibiotic use early in disease may be warranted for these high-risk characteristics among CRE infections, with recent research in CRE bacteremia showing positive outcomes ( 25 ). Research should continue on carbapenem-resistant Enterobacterales infections in large, randomized cohorts and case-control studies to further identify best practices to promote treatment success.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 28 eligible studies were included. 11,13,21,26,31,32,36,[38][39][40][41]43,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] The characteristics of the studies are presented in Table 4. Only studies that reported mortality as a treatment outcome were presented.…”
Section: Antimicrobial Regimens Characteristics Of Included Studiesmentioning
confidence: 99%
“…Overall, this may lead to a decrease in mortality, shorter hospital stays, and a reduction in hospitalization costs [44][45][46][47]. Rapid diagnostics is associated with early intervention with effective antimicrobial therapy which may lead to improved clinical outcomes and decreased mortality [48].…”
Section: Early and Appropriate Use Of Ceftazidime-avibactammentioning
confidence: 99%